Answer :

(i) Given that: 1 + 64x3


= 1 + (4x)3


= (1 + 4x)[(1)2 βˆ’ (1)(4x) + (4x)2]


[∡ a3 + b3 = (a + b)(a2 – ab + b2) ]


= (1 + 4x)(1 – 4x + 16x2)


(ii) Given that: a3 βˆ’ 2√2b3


= (a)3 βˆ’ (√2b)3


= (a βˆ’ √2b) [(a)2 + (a)(√2b) + (√2b)2]


[∡ a3 – b3 = (a + b)(a2 + ab + b2) ]


= (a βˆ’ √2b)(a2 + √2ab + 2b2)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics